Why Do We Need Environmental Monitoring for Everglades Restoration? - Frank J. Mazzotti; Nicola Hughes; Rebecca G. Harvey (EDIS, 2008)
WEC-241, a 3-page illustrated fact sheet by Frank J. Mazzotti, Nicola Hughes, and Rebecca G. Harvey, explains what environmental monitoring is, its scientific basis, how it relates to adaptive management, its cost effectiveness, and what it means for the Everglades Restoration Plan. Includes references. Published by the UF Department of Wildlife Conservation and Ecology, November 2007.